Derivation of the material models for ultra-high molecular-weight polyethylene fiber-reinforced armor-grade composites with different architectures. Issue 3 (3rd May 2016) - Grujicic, Mica; Snipes, Jennifer; Ramaswami, S.; Avuthu, Vasudeva; Yen, Chian-Fong; Cheeseman, Bryan
Abstract : Purpose: – To overcome the problem of inferior through-the-thickness mechanical properties displayed by armor-grade composites based on two-dimensional (2D) reinforcement architectures, armor-grade composites based on three-dimensional (3D) fiber-reinforcement architectures have recently been investigated experimentally. The paper aims to discuss this issue. Design/methodology/approach: – The subject of the present work is armor-grade composite materials reinforced using ultra-high-molecular-weight polyethylene fibers and having four (two 2D and two 3D) prototypical architectures, as well as the derivation of the corresponding material models. The effect of the reinforcement architecture is accounted for by constructing the appropriate unit cells (within which the constituent materials and their morphologies are represented explicitly) and subjecting them to a series of virtual mechanical tests (VMTs). The results obtained are used within a post-processing analysis to derive and parameterize the corresponding homogenized-material models. One of these models (specifically, the one for 0°/90° cross-collimated fiber architecture) was directly validated by comparing its predictions with the experimental counterparts. The other models are validated by examining their physical soundness and details of their predictions. Lastly, the models are integrated as user-material subroutines, and linked with a commercial finite-element package, in order to carry out a transient non-linear dynamics analysis of ballistic transverse impact of armor-grade composite-material panels with different reinforcement architectures. Findings: – It is found that the reinforcement architecture plays a critical role in the overall ballistic limit of the armor panel, as well as in its structural and damage/failure response. Originality/value: – To the authors' knowledge, the present work is the first reported attempt to assess, computationally, the utility and effectiveness of 3D fiber-reinforcement architectures for ballistic impact applications.